2017
DOI: 10.3390/nu9121363
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina Extract Enhanced a Protective Effect in Type 1 Diabetes by Anti-Apoptosis and Anti-ROS Production

Abstract: Interest in the nutritional value and pharmacological activities of blue-green algae has gradually increased. Spirulina extracts show protective effects against apoptosis and inflammatory damage in various cell types. Here, we investigated the protective effects of extracts from Spirulina maxima in a cytokine-mediated type 1 diabetes model in vitro and in streptozotocin-induced diabetic Wistar rats in vivo. Interleukin-1β and interferon-gamma induced substantial cytotoxicity to RINm5F rat insulinoma cells, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 58 publications
2
14
0
3
Order By: Relevance
“…The reduction of nitrite production in different tissues such as brain, heart and liver in our study could be considered an important factor of protection against oxidative damage to DNA, indicating its important protective effect against STZ-induced damage and these results are corroborated by numerous researchers who have studied the antioxidant and anti-inflammatory properties of SPI [35] [36] [37]. Many of the studies investigating the antioxidant effect of SPI have attributed this property to phycocyanin since this phycobilin pigment has radical scavenging properties, noting that some of these reports have also shown that phycocyanin directly inhibits NAD(P)H oxidase activity [38] [39] and that NAD(P)H oxidases may be the main source of ROS in the tissues of diabetic animals and patients [40] [41].…”
Section: Discussionsupporting
confidence: 83%
“…The reduction of nitrite production in different tissues such as brain, heart and liver in our study could be considered an important factor of protection against oxidative damage to DNA, indicating its important protective effect against STZ-induced damage and these results are corroborated by numerous researchers who have studied the antioxidant and anti-inflammatory properties of SPI [35] [36] [37]. Many of the studies investigating the antioxidant effect of SPI have attributed this property to phycocyanin since this phycobilin pigment has radical scavenging properties, noting that some of these reports have also shown that phycocyanin directly inhibits NAD(P)H oxidase activity [38] [39] and that NAD(P)H oxidases may be the main source of ROS in the tissues of diabetic animals and patients [40] [41].…”
Section: Discussionsupporting
confidence: 83%
“…The two bands were analyzed by Q-TOF MS/MS. The results revealed that the 20 kDa band didn't correspond to any known protein while the ~16 kDa protein band was C-phycocyanin α chain, which has many pharmacological benefits (34). To investigate the effects of SPCP on the viability of CCD-986sk cells, an MTS assay on cells treated with various doses of SPCP was performed.…”
Section: Resultsmentioning
confidence: 99%
“…However, the OT extract at 5 µg/mL did not affect the increased IL1-β mRNA transcription induced by 2 µM B[a]P. These results showed that the microalgal extracts could inhibit the gene expression of several pro-inflammatory cytokines induced by B[a]P in endothelial cells. [59,60], and it is also known that microalgal extracts can inhibit apoptosis in cancerous cells [61], we therefore decided to evaluate apoptosis after exposure for 24 h to B[a]P or microalgal extracts (0.1 and 5 µg/mL) alone or in co-exposure. This was performed by using fluorescence microscopy after Hoechst staining ( Figure 5).…”
Section: Effect Of P Tricornutum or O Tauri Extracts On Gene Expresmentioning
confidence: 99%